KUALITAS KIMIA DAN FISIK SUSU KAMBING SAANEN PASTEURISASI PADA LAMA PENYIMPANAN BERBEDA DALAM REFRIGERATOR - Andrijal Silaban; Sista Rizqiana; Nursyam Andi Syarifuddin; Anis Wahdi (JURNAL PENELITIAN PETERNAKAN LAHAN BASAH, 2023)
This study aims to determine the effect of storage time of pasteurized saanen goat milkstored in the refrigerator. The experimental method used a completely randomized design withfour treatments and five replications. Sampling was carried out on the morning of milking asmuch as 4 l at CV. A series of Ark Awards, Mandiangin, Banjar district, South Kalimantan.Then pasteurized LTLT at 65°C for up to 30 minutes. Then put a 200 ml bottle and put it in therefrigerator 4°C. The prepared milk samples were immediately analyzed using a lactoscan. Theresults showed that pasteurized saanen goat milk stored in the refrigerator is suitable forconsumption up to 8 days in terms of protein content, fat content, lactose, freezing point anddegree of acidity (pH) and specific gravity is suitable for consumption up to 12 days.